Improving the dynamic and seismic behaviour of rigid block-like elements through active mass dampers. (15th January 2023) - Di Egidio, Angelo; Olivieri, Carlo; Contento, Alessandro; Pagliaro, Stefano
Abstract: Several researchers proposed innovative techniques for the improvement of the dynamic and seismic performances of rigid block-like elements. These techniques were mostly based on passive control methods, such as base isolation or the use of tuned mass dampers and dynamic mass absorbers. Only a few researchers studied active control methods applied to the dynamics of rigid blocks. This paper proposes an active control method for rigid block-like elements based on the Pole Placement Method algorithm, which is used to drive a mass running on the top of the rigid block-like elements. The optimal control law obtained with the Pole Placement Method is obtained starting from the linearised equation of motion. The effectiveness of the proposed control method is investigated comparing the behaviour of rigid block-like elements with and without active control under harmonic and seismic excitation. The results are summarised in overturning spectra, in the case of harmonic excitation, and rocking maps, in the case of seismic excitation. Preliminary analyses show that the control law has good robustness with respect to the time-delays and a unique setting of the control coefficient is able to provide good performances in wide ranges of the geometrical characteristics of the rigid block-like element. Finally, results show the effectiveness of the proposed active control method for both harmonic and seismic excitations. Highlights: The paper proposes an active control method based on the Pole Placement Method The optimal control law is obtained starting from the linearised equations of motion The effectiveness of the control is investigated under harmonic and seismic excitation The analyses show that the control law has good robustness with respect to time delays The results show the effectiveness of the proposed active control method